Women Empowerment through Cooperative: A Case Study of Ichangu Mahila Jagriti Multipurpose Cooperative Limited - Koirala, Padma (Ganeshman Darpan, 2023)
Women empowerment involves participation of women in political structures and formal decision-making and economic decision-making which is achieved through education, raising awareness, literacy, and training. Co-operatives in general and specifically women-led co-operatives, have played an important role in women empowerment. This study aims to identify the contribution of Ichangu Mahila Jagriti Multipurpose Co-operative Limited (IMJCL) located in Nagarjun municipality Kathmandu on economic, socio-cultural and political aspects of women empowerment who became its member. The study was conducted in Nagarjun municipality Kathmandu among the 124 women inheritors with 10 years of experiences and cooperative activities were randomly selected using lottery method for data collection. Primary data was collected via structured questionnaire, focus group discussion and key informant interviews. For the data analysis paired sample t-test was applied in three different domains of empowerment: economic, socio-cultural and political dimensions. The finding showed there was positive impact on women empowerment with significant difference in socio-cultural, economic and political empowerment of its member. The study shows there were significant changes after involvement in different programmes of IMJCL. Finally, its finding focusses on the crucial role of cooperative in the overall empowerment of women. Extension of cooperative organizations is indispensable for the nation.